Degradation of Anode-Supported Solid Oxide Fuel Cells under Load Trip and Cycle Conditions and Their Degradation Prevention Operating Logic. Issue 9 (22nd June 2018) - Kim, You-Dong; Lee, John-In; Saqib, Muhammad; Park, Ka-Young; Hong, Jongsup; Yoon, Kyung Joong; Lee, Insung; Park, Jun-Young
Abstract : To design durable and reliable solid oxide fuel cells (SOFCs) for commercialization, we investigate the degradation behavior of yttria-stabilized zirconia-based anode-supported cells under two electrical load conditions – load trip (0.2–0 A·cm −2 ) and load cycle (0.20–0.12 A·cm −2 ) modes for 60 times (about 1, 450 h). During the load trip condition, the operating voltage of the cell decreases by 86 mV through the 1, 443 h operation (60 load trips) with the degradation ratio of 9.1% (59.5 μV·h −1 at 0.2 A·cm −2 ), while the cell voltage decreases with the different degradation ratios of 7.1% and 4.2% at 0.2 and 0.12 A·cm −2, respectively, during the 60 load cycles (49.4 μV·h −1 at 0.2 A·cm −2 ). A combination of electrochemical impedance spectroscopy and distribution function of relaxation times, thermochemical (Gibbs equilibrium calculations), and post-mortem analysis (field emission-scanning electron microscopy and electron probe micro-analysis with an energy dispersive X-ray spectroscopy) demonstrates the main degradation mechanism of SOFCs under dynamic electrical load conditions. Furthermore, an operation strategy to mitigate the performance degradation under dynamic electrical loads is proposed through the identification of weak points of SOFC components.